Analisis Konsepsi Perbandingan Pembinaan Akhlak Menurut Al-Ghazali Dan Ibnu Khaldun - Rahimi (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2022)
Abstract : This paper examines the comparison of moral development between Al-Ghazali and Ibn Khaldun. With the aim of knowing the conception of methods in Islamic education, to know education, to find out the concept of building morality according to Al-Ghazali, to find out the concept of building morality according to Ibn Khaldun, to find out the comparison of the concept of building morality according to Al-Ghazali and Ibn Khaldun. This study was conducted using the library research method. The results of this study indicate that moral development according to Al-Ghazali can be carried out by providing examples, habituation, training, suggestions and prohibitions, then given an explanation and understanding according to his level of thinking about social, moral and religious norms and values. Then grow your actions, attitudes, views, convictions and awareness and trust to do something responsible. Meanwhile, according to Ibn Khaldun, moral development is reflected in his thoughts in education. Moral development is carried out by preparing a person in terms of morals, namely growing and forming a perfect human personality through noble and noble morals.